Musikalische Praxis als Lebensform Sinnfindung und Wirklichkeitserfahrung beim Musizieren - Houben, Eva-Maria (Musik und Klangkultur, 2018)
The practice of making music as an act of liberation from perfection and productivity - and as the experience of meaningfulness in a specific situation, a specific location, in relationships.